The control of a state of the static and dynamical posture of a person doing physical exercises - Kashuba, Vitaliy; Lopatskyi, Serhii (Journal of Education, Health and Sport, 2017)
Actuality. Movements are the vital human potential that ensures the normal functioning of its organism as a complex biological system. Humans as a biological object during its development is subjected to numerous influences of the external environment, and it often leads to significant changes in internal processes and interactions in its body.Objectives of research: to provide information regarding the peculiarities of development different kindes of technologies for diagnostics the level of biomechanical properties of the human foot.Results of research. The foot as one of the most important organs of human walking in the conditions of natural locomotives performs not only the support function, but also provides the organization of spring interactions of the human body with a resisting surface. Different diseases and damage of organs of the locomotor system are often accompanied by serious functional disorders of the human motor apparatus, decreased muscle strength and tone, loss the ability of normal movement, and ultimately leads to permanent loss of disability and invalidity.Conclusions. The human body in the orthogonal position has a system of complex mechanisms that provide support conditions through the morphofunctional components of the lower limb, in particular, the foot. The foot is the most important structural element of the musculoskeletal system, which provides its stato-motor function and is an integral morphofunctional object, on which the motor function of a person depends. It was considered biomechanical control as a way of determining the qualitative and quantitative characteristics of the motor function of the lower limbs of a person in the course of the age development.The further research will be associated with the development of information and methodological system aimed on measuring the state of spatial organization of the human body in the process of physical education.